PENGARUH FINANCING TO DEPOSIT RATIO DAN BEBAN OPERASIONAL TERHADAP PENDAPATAN OPERASIONAL TERHADAPPROFITABILITAS DENGAN NON PERFOMING FINANCING SEBAGAI VARIABEL PEMODERASI PADA BANK UMUM SYARIAH YANG TERDAFTAR DI OTORITAS JASA KEUANGAN PERIODE 2016-2022 - Hera, Wat (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2024)
This research aims to examine the influence of Financing to Deposit Ratio (FDR) and Operational Expenses to Operating Income Ratio (BOPO) on Profitability with Non-Performing Financing (NPF) as a moderating variable. The population in this study consists of Sharia commercial banks listed in the Financial Services Authority (OJK) during the period 2016-2022, totaling 13 companies. The study utilizes quantitative data, and secondary data were obtained from the www.ojk.go.id website and annual reports of the companies. Sample selection used purposive sampling with a total of 60 data points from 12 companies for each period. Structural Equation Modeling-Partial Least Square (SEM-PLS) was employed to analyze the data. The research results indicate that Financing to Deposit Ratio (FDR) does not significantly influence Profitability. Operational Expenses to Operating Income Ratio (BOPO) has a negative and significant impact on Profitability. Non Performing Financing (NPF) is unable to moderate the relationship between Financing to Deposit Ratio (FDR) and Profitability. Non Performing Financing (NPF) is unable to moderate the relationship between Operational Expenses to Operating Income Ratio (BOPO) and Profitability. Keywords: Financing to Deposit Ratio (FDR), Operational Expenses to Operating Income Ratio (BOPO), Profitability, Non Performing Financing (NPF)